Risk factors of subclinical hypothyroidism and the potential contribution to miscarriage: A review - Shuhei So; Fumiko Tawara (Reproductive Medicine and Biology, 2020)
Abstract Background There is no clear cutoff value for thyroid‐stimulating hormone (TSH) level that defines subclinical hypothyroidism (SCH). Moreover, TSH levels can be affected by numerous factors. Although mild SCH has been implicated in miscarriage, the relationship between TSH levels and miscarriage remains unelucidated. Methods We reviewed nine known risk factors affecting TSH levels and 28 studies investigating the potential association between mild SCH and miscarriage, examining whether these factors were considered. Main findings Among 28 studies that examined whether mild SCH (TSH > 2.5 mIU/L) contributed to miscarriage, thyroid antibodies were measured in only 15. TSH measurement methods were described in 18 studies. Although the iodinated contrast medium used in hysterosalpingography (HSG) is stored in the body for a long time and is a risk factor for mild SCH, only one study described its potential impact on TSH levels. Nine studies, which concluded that mild SCH contributed to miscarriage, had thyroid status evaluated only after the onset of pregnancy, but not before. Conclusion TSH levels can be significantly affected by patient demographics and health history, country of origin, and fertility treatment. It is important to consider these factors while evaluating mild SCH. It remains unclear how mild SCH contributes to miscarriage.